Detection of DNA hypomethylation mediated floral induction in Longan and Spinach using the HAT-RAPD technique - S. Anuntalabhochai (2018)
In this study, the HAT-RAPD technique was used to detect DNA methylation in the four plant species, rice (Oryza sativa), petunia (Petunia hybrida), spinach (Spinacea oleracea L.) and longan (Dimocarpus longan Lour.), which were treated using 5-azacytidine, potassium chlorate (KClO3) and a low temperature induction. Rice and petunia were chosen to be induced because in these species it is known that 5-azacytidine is able to induce hypomethylation in their genomes leading to morphological changes, in particular floral induction, in the developing plants. Using the HAT-RAPD technique, DNA methylation was detected using the restriction enzymes HpaII and MspI in rice and petunia (as expected) and in spinach, but was found to be absent in longan, which suggests that floral induction in longan is undetectable in longan. © 2009 Science Publications.